2021
DOI: 10.3390/ijms22052570
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Conditions Promote Rhythmic Contractile Oscillations Mediated by Voltage-Gated Sodium Channels Activation in Human Arteries

Abstract: Arterial smooth muscle exhibits rhythmic oscillatory contractions called vasomotion and believed to be a protective mechanism against tissue hypoperfusion or hypoxia. Oscillations of vascular tone depend on voltage and follow oscillations of the membrane potential. Voltage-gated sodium channels (Nav), responsible for the initiation and propagation of action potentials in excitable cells, have also been evidenced both in animal and human vascular smooth muscle cells (SMCs). For example, they contribute to arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…Our data showed that Na V channels are expressed in both endothelium and media of murine FOMA and CA in agreement with previous investigations performed on murine cremaster arteries [ 13 ], human subcutaneous arterioles [ 21 ], and human uterine arteries [ 15 ]. Our RT-qPCR data indicate that scn2a , encoding Na V 1.2, is the most abundant Na V channel α-subunit gene expressed in both aorta and MA.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our data showed that Na V channels are expressed in both endothelium and media of murine FOMA and CA in agreement with previous investigations performed on murine cremaster arteries [ 13 ], human subcutaneous arterioles [ 21 ], and human uterine arteries [ 15 ]. Our RT-qPCR data indicate that scn2a , encoding Na V 1.2, is the most abundant Na V channel α-subunit gene expressed in both aorta and MA.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, scn2b and scn3b are also expressed but to a much lower extent. Indeed, the expression of Na V β subunits has hardly ever been studied in arteries, but similar to our data, scn1b , scn2b , and scn3b expressions have been reported in rat aorta [ 6 ], while scn1-4b are expressed in human uterine arteries [ 15 ]. Altogether, it seems that the expression profile of the Na V channel gene in arteries is different in rodents and humans.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results presented herein are interesting, and they hence led us to propose that, in concert with its antagonistic action of mineralocorticoid receptor, the exposure to esaxerenone may directly modify the magnitude, gating properties, and Hys (V) strength of I Na present in different excitable cells. It also needs to be mentioned that the activity of Na V channels has been found to be functionally expressed in various types of vascular smooth muscles [ 84 , 85 ]. Therefore, it is worth pursuing to a further extent as to which esaxerenone-induced antihypertensive action [ 78 , 79 ] is associated with its additional inhibitory action on I Na (i.e., Na V 1.7-encoded current) inherently in vascular smooth myocytes.…”
Section: Hys (V) Behavior Residing In Persistent N...mentioning
confidence: 99%